Magnetic resonance imaging of posterolateral plica of the elbow joint: Asymptomatic vs. symptomatic subjects. - Sang-Hee Choi; Suk Kyeong Ji; Seung Ah Lee; Min Jong Park; Moon Jong Chang (PLoS ONE)
Background Magnetic resonance imaging (MRI) may be useful to diagnose a posterolateral plica syndrome of the elbow joint because this syndrome has less clear clinical features. The purposes of this study were to document mediolateral and sagittal dimensions of a posterolateral synovial fold and to determine the proportion of subjects with the posterolateral plica in asymptomatic elbows. We also aimed to determine whether the dimensions of the posterolateral synovial fold and the prevalence of the plica differ between symptomatic and asymptomatic subjects. Materials and methods This retrospective review of prospectively collected data included 50 asymptomatic elbows (asymptomatic group) and 14 elbows with arthroscopically confirmed posterolateral plicae (plica group). The mediolateral and sagittal dimensions of the posterolateral synovial fold were measured. In addition, the criteria for the prevalence of posterolateral plica was determined with conventional MRI as synovial fold dimension ≥ 3 mm and coverage of radial head by synovial fold ≥ 30%. Results The plica group showed larger posterolateral synovial fold dimensions compared to the asymptomatic group. The median mediolateral and sagittal dimensions of the synovial fold in the asymptomatic group were 3.8 mm and 4.7 mm, respectively. Dimensions in the plica group were 7.0 mm and 7.4 mm, respectively. When the presence of posterolateral plica was determined using the dimension criteria, there was no difference in the prevalence of the plica between the asymptomatic and the plica group. However, using the coverage criteria, the prevalence of posterolateral elbow plica was significantly greater in the plica group than the asymptomatic group (64% vs. 18%; p < 0.001). Conclusions The patients who underwent arthroscopic surgery for posterolateral plica syndrome had larger dimensions of the posterolateral synovial fold and higher prevalence of the posterolateral plica on conventional MRI compared to the asymptomatic subjects.